2019
DOI: 10.3390/s19061392
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the UHF Signals Generated by Partial Discharges in Mineral Oil

Abstract: The paper presents the results of the analysis on the variability of the ultra-high frequency (UHF) signals generated by partial discharges (PD) under the long-term AC voltage. Surface PD (SD) are generated by model PD source (PDS) immersed in brand new mineral oil. Three scenarios are compared and investigated, where different solid dielectrics are applied: pressboard paper (PBP), polytetrafluoroethylene (PTFE) and glass-ceramic (GLS). The PDS is powered continuously by the AC voltage with its relative level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Under aeronautic conditions, however, the most accurate methods are be those based on EM radiation detection. Special attention should be paid to the detection of high-energy radiation [21] and the very popular UHF method [22,23], which extend the range of EM wavelength detection to longer and shorter wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Under aeronautic conditions, however, the most accurate methods are be those based on EM radiation detection. Special attention should be paid to the detection of high-energy radiation [21] and the very popular UHF method [22,23], which extend the range of EM wavelength detection to longer and shorter wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement systems and methodology are presented, e.g., in [16,17]. The electromagnetic radiation coming from PD is also registered in the Ultra high frequency (UHF) range [18] and high ionizing energies [19,20]. Not only measuring devices, systems, and methods, but also all kinds of descriptors have been developed to assess the damage in both liquid and gas and solid insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Combined UHF and acoustic sensors have been investigated to reduce the negative effect of the stiff structure of the transformer tank on acoustic signals and, therefore, increase the accuracy of PD localization [20,21]. Experimental investigations showed that the UHF method can detect small PD levels with good sensitivity [22,23], even when they are buried within insulation layers [24]. In contrast, the acoustic method can detect small PD levels only when the PD is in direct line of sight of the sensor [24].…”
Section: Introductionmentioning
confidence: 99%